La Gestión financiera y la rentabilidad de la empresa de servicios turisticos "Hostería Arrayan y Piedra" de la ciudad de Macas – Ecuador periodo 2015 – 2018 - Katerin Jajaira, Garcés Quizhpi (2019)
The present research work aims to evaluate the financial management and profitability of the tourism services company Hosteria Arrayan and Piedra of Macas city - Ecuador during the period 2015 – 2018. For which the analytical - synthetic method was used by the non-experimental design descriptive research approach; identifying as the study population, in the one hand, the financial statements to which the content analysis technique was applied. On the other hand, the owner and accountant manager were selected on behalf of the 22 permanent and temporary workers of the inn to gather complementary information on financial management through the application of a survey and the technique of direct observation. The main results of the investigation reveal that the company has liquidity problems and high levels of debt and low effect in the use of its assets, have led to low profitability levels reported, it is mainly proposed to apply short-term policies for the adequate management of credit and working capital, and long-term policies for progressive reduction of debt, which help to reverse this situation.